2011
DOI: 10.1007/s10803-011-1205-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Autism Spectrum Disorder and Attention Deficit Hyperactivity Disorder by Means of Inhibitory Control and ‘Theory of Mind’

Abstract: Autism spectrum disorders (ASD) and attention deficit hyperactivity disorders (ADHD) are both associated with deficits in executive control and with problems in social contexts. This study analyses the variables inhibitory control and theory of mind (ToM), including a developmental aspect in the case of the latter, to differentiate between the disorders. Participants with an ASD (N = 86), an ADHD (N = 84) and with both disorders (N = 52) in the age range of 5-22 years were compared. Results were differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 63 publications
(76 reference statements)
6
42
0
1
Order By: Relevance
“…Some have proposed that both ADHD and ASD are part of a category of 'empathy disorders' [130]. Other research [131][132][133], however, suggests that children with ADHD are not as impaired as children with ASD on theory of mind tasks.…”
Section: Neuropsychological/cognitivementioning
confidence: 99%
“…Some have proposed that both ADHD and ASD are part of a category of 'empathy disorders' [130]. Other research [131][132][133], however, suggests that children with ADHD are not as impaired as children with ASD on theory of mind tasks.…”
Section: Neuropsychological/cognitivementioning
confidence: 99%
“…Some studies evidence that the comorbid group is the group with the most pronounced brain function abnormalities (Chantiluke et al, 2014) and more impaired on daily-life executive functioning (Dajani et al, 2016). Similarly, studies that had focused on response inhibition report that ADHD and ASD+ADHD patients show more dysfunction on inhibitory control compared to the ASD patients (Bühler et al, 2011;Sinzig et al, 2008b;Tye et al, 2014). In addition, even studies that do not find differences between the clinical groups on response inhibition suggest a tendency of decreased performance in the comorbid group (Neely et al, 2016;Pitzianti et al, 2016;Takeuchi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences between clinical groups on inhibit performances were found in three studies (Neely, Green, Sciberras, Hazell, & Anderson, 2016;Pitzianti et al, 2016;Takeuchi et al, 2013). In three studies, ADHD and ASD+ADHD patients demonstrated more impairment in inhibitory control compared to the ASD patients (Bühler et al, 2011;Sinzig, Morsch, Bruning, Schmidt, & Lehmkuhl, 2008b;Tye et al, 2014). In one study, the ASD+ADHD group had more deficits on inhibition compared to other groups (Chantiluke et al, 2014 Pitzianti et al (2016) found the ADHD+HFA was impaired on response inhibition when compared with the TD group using a computerized task of Go/No-Go.…”
Section: Response Inhibitionmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, ADHD and ASD are highly comorbid and both disorders share similar neurocognitive deficits, including poor theory of mind. 28 Several studies have pointed out that there are altered blood vasopressin levels in ASD. 4,29 Furthermore, a recent study reported a positive correlation between plasma vasopressin levels and theory of mind ability in ASD subjects and posited that blood vasopressin levels are a robust biomarker of theory of mind ability in children with ASD.…”
Section: Discussionmentioning
confidence: 99%